La revitalisation d’un quartier historique « Le cas du quartier R’hiba à Tlemcen » - FRAHTA Raihana; Pr. ZEGHLECHE, Hamza (Encadreur); Mme OMARI, Asia (Co-Encadreur) (Université Ferhat Abbas Sétif 1. Institut d'architecture et sciences de la terre. Département d'architecture, 2015)
this dissertation is the outcome of a work that examine the problem of the degradation of an urban heritage and architectural, and also the failure of the restoration and the rehabilitation work of historical neighborhoods in Tlemcen. An example of a historical medina arabo- mauresque need protection and preservation of its heritage. R'hiba is an ancient neighborhood in Tlemcen, a historical residential district rich with local heritage. it suffer from the degradation of the built environment, as it suffer from the marginalization by its inhabitants. All these problems lead to interventions on differents domains economic, social, cultural; and environmental. The purpose of these interventions is to revive R'hiba city, integrating new projects that helps to reach the objective, and using a method based on the analysis of different approaches( historically we study the growth of the district, morphologically, functionally...). This study will reveal the alternatives and the interventions proposals that ensure the revitalization, the improvement, and the preservation of this historical district .
هذه المذكرة هي نتيجة العمل على دراسة المشكلة تدهور التراث العمراني والمعماري، وفشل ترميم وإعادة تأهيل الأحياء التاريخية في تلمسان، فهي مدينة تاريخية ومثال حي لمعالم مدينة عربية ذات طابع اندلسي، و التي تتطلب وتستوجب حماية و حفظ و صون تراثها، ونأخذ على سبيل المثال الحي القديم لتلمسان « الرحيبة « الذي هو عبارة عن حي تاريخي ذو طابع سكني غني بالتراث المحلي للمنطقة، لكن هذا الحي يخضع لتدهور البيئة العمرانية وايضا تم تهميشه من قبل السكان المحليين. جميع هذه المشاكل تؤدي إلى التدخلات في مختلف المجالات الاقتصادية والاجتماعية والثقافية و البيئية. تهدف هذه التدخلات الى اعادة احياء « الرحيبة « وذلك بدمج المشاريع الجديدة والتي بدورها تساهم في تحقيق هذا الهدف، ولهذه الدراسة سوف نستخدم طريقة تحليل مناهج مختلفة ( تاريخيا لا بد من دراسة نمو هذا الحي، شكليا، وظيفيا ...) هذه الدراسة ستسمح بمعرفة البدائل و المقترحات للتدخلات التي تضمن و تؤكد اعادة احياء وتحسين هذا الحي التاريخي و المحافظة عليه.
Keywords: Patrimoine Urbain et Architectural; Villes historiques; R’hiba; Revitalisation; Intervention